Influence of Microclimate Factors on Halyomorpha halys Dehydration - Francesca Grisafi; Giulia Papa; Mario Barbato; Sergio Tombesi; Ilaria Negri (Insects, 2021)
Understanding the interaction between insects and microclimate can be essential in order to plan informed and efficient treatments against agricultural pests. Microclimatic factors such as humidity and temperature can influence the population dynamics of the invasive agricultural pest Halyomorpha halys, the brown marmorated stink bug. The aim of this work was to evaluate the level of transpiration of H. halys in dry, normal and humid microclimates according to the sex, physiological conditions and developmental stage of individuals. Water loss during diapause and the effect of population density on insects’ transpiration were also assessed, as were the nutritional preferences of adults upon exiting diapause. Our data demonstrate that microclimatic conditions significantly influence the transpiration of this pest species. The effect of sex and feeding status on insects’ water loss is marked, while population density does not influence water loss in diapausing individuals. The first nutritional need of the overwintering generations is represented by hydration, likely due to the water loss during diapause.